The poly(ADP-ribosyl)ation of BRD4 mediated by PARP1 promoted pathological cardiac hypertrophy - Zhenzhen Li; Zhen Guo; Rui Lan; Sidong Cai; Zhirong Lin; Jingyan Li; Junjian Wang; Zhuoming Li; Peiqing Liu (Elsevier, 2021)
The bromodomain and extraterminal (BET) family member BRD4 is pivotal in the pathogenesis of cardiac hypertrophy. BRD4 induces hypertrophic gene expression by binding to the acetylated chromatin, facilitating the phosphorylation of RNA polymerases II (Pol II) and leading to transcription elongation. The present study identified a novel post-translational modification of BRD4: poly(ADP-ribosyl)ation (PARylation), that was mediated by poly(ADP-ribose)polymerase-1 (PARP1) in cardiac hypertrophy. BRD4 silencing or BET inhibitors JQ1 and MS417 prevented cardiac hypertrophic responses induced by isoproterenol (ISO), whereas overexpression of BRD4 promoted cardiac hypertrophy, confirming the critical role of BRD4 in pathological cardiac hypertrophy. PARP1 was activated in ISO-induced cardiac hypertrophy and facilitated the development of cardiac hypertrophy. BRD4 was involved in the prohypertrophic effect of PARP1, as implied by the observations that BRD4 inhibition or silencing reversed PARP1-induced hypertrophic responses, and that BRD4 overexpression suppressed the anti-hypertrophic effect of PARP1 inhibitors. Interactions of BRD4 and PARP1 were observed by co-immunoprecipitation and immunofluorescence. PARylation of BRD4 induced by PARP1 was investigated by PARylation assays. In response to hypertrophic stimuli like ISO, PARylation level of BRD4 was elevated, along with enhanced interactions between BRD4 and PARP1. By investigating the PARylation of truncation mutants of BRD4, the C-terminal domain (CTD) was identified as the PARylation modification sites of BRD4. PARylation of BRD4 facilitated its binding to the transcription start sites (TSS) of hypertrophic genes, resulting in enhanced phosphorylation of RNA Pol II and transcription activation of hypertrophic genes. The present findings suggest that strategies targeting inhibition of PARP1-BRD4 might have therapeutic potential for pathological cardiac hypertrophy.